2006
DOI: 10.1088/0031-8949/73/4/015
|View full text |Cite
|
Sign up to set email alerts
|

Lifetimes of highly excited atomic states

Abstract: We consider a highly excited atom in a good cavity strongly pumped by coherent light. We derive the autocorrelation function of the field emergent from the cavity. We show that the autocorrelation function can be expressed in terms of the atomic dissipation rate. In order to distinguish between the resonant and the non-resonant case, we introduce a parameter interpreted as the measure of the relative detuning between the pump laser and the excited atom frequency. By selecting the parameter time, we determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The last term describes the external driving where and design respectively the amplitude and frequency of the coherent field. In this work, we focus on the resonant condition without nonlinear dissipations [ 57 ], and the master equation is expressed as [ 58 , 59 , 60 , 61 , 62 ] …”
Section: Physical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The last term describes the external driving where and design respectively the amplitude and frequency of the coherent field. In this work, we focus on the resonant condition without nonlinear dissipations [ 57 ], and the master equation is expressed as [ 58 , 59 , 60 , 61 , 62 ] …”
Section: Physical Modelmentioning
confidence: 99%
“…The second approximation is to limit the number of excitations inside the cavity. In the WER, we can write the wave function as a superposition of product of excitonic and photonic states and retain up to four states, which can be justified by the excitation of the cavity [ 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ] …”
Section: Physical Modelmentioning
confidence: 99%
“…It is shown that these effects give rise to small corrections as compared to the nonlinear exciton-exciton scattering [41,50,51]. Furthermore, we assume that the thermal reservoir is at the T = 0 and we neglect the nonlinear dissipations [52], then the master equation can be written as [53][54][55][56][57] …”
Section: Modelmentioning
confidence: 99%
“…In this section, we explore the case of highly excited Rydberg atom. In the previous work, we have shown that the expression of the autocorrelation function in the strong coupling regime is: [25] g (2) (τ ) = 1 + µ e −τ /τpop − (µ + 1) cos(Ωτ ) e −τ /τ coh , (14) where µ is a parameter given by: µ…”
Section: Highly Excited Rydberg Atom In a Cavitymentioning
confidence: 99%